2014
DOI: 10.1186/1471-2466-14-159
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported exercise and longitudinal outcomes in cystic fibrosis: a retrospective cohort study

Abstract: BackgroundCystic fibrosis (CF) is characterized by recurrent respiratory infections and progressive lung disease. Whereas exercise may contribute to preserving lung function, its benefit is difficult to ascertain given the selection bias of healthier patients being more predisposed to exercise. Our objective was to examine the role of self-reported exercise with longitudinal lung function and body mass index (BMI) measures in CF.MethodsA total of 1038 subjects with CF were recruited through the U.S. CF Twin-Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Interestingly, regular exercise was associated with a reduced FEV1 decline in the adult participants but not in children aged 10-17 years old. 29 Schneidermann et al 4 nicely reproduced this positive effect of regular physical activity on lung function decline in a longitudinal study. The Habitual Activity Estimation Scale (HAES) was completed at each quarterly clinical visit in 212 children aged 7-17 years over a period of 9 years.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Interestingly, regular exercise was associated with a reduced FEV1 decline in the adult participants but not in children aged 10-17 years old. 29 Schneidermann et al 4 nicely reproduced this positive effect of regular physical activity on lung function decline in a longitudinal study. The Habitual Activity Estimation Scale (HAES) was completed at each quarterly clinical visit in 212 children aged 7-17 years over a period of 9 years.…”
Section: Discussionmentioning
confidence: 84%
“…Participation in regular exercise was associated with older age at the time of study and a higher FEV1 but not with CFTR genotype or exocrine pancreatic function. Interestingly, regular exercise was associated with a reduced FEV1 decline in the adult participants but not in children aged 10–17 years old . Schneidermann et al nicely reproduced this positive effect of regular physical activity on lung function decline in a longitudinal study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Exercise has been shown to influence lung function positively in CF patients if carried out in a beneficial, safe and monitored environment [191, 192]. Spiritual factors interestingly have been shown to contribute positively on treatment adherence in CF patients [193].…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have reported on the long-term relationship between physical activity and clinical outcomes, in particular lung function, in people with CF. C ollaco et al [ 11 ], using US CF Foundation patient registry data, found adults who self-reported any exercise participation had a slower rate of decline in FEV 1 over 5 years. In a predominantly paediatric cohort, participants who were categorised as having higher levels of activity, based on self-report using the Habitual Activity Estimation Scale, had a slower rate of decline in FEV 1 over an average of 5-years of follow-up [ 2 ].…”
mentioning
confidence: 99%